2021
DOI: 10.1002/mds.28787
|View full text |Cite
|
Sign up to set email alerts
|

Coding and Noncoding Variation in LRRK2 and Parkinson's Disease Risk

Abstract: A BS TRACT: Background: The leucine-rich repeat kinase 2 (LRRK2) gene harbors both rare highly damaging missense variants (eg, p.G2019S) and common noncoding variants (eg, rs76904798) with lower effect sizes that are associated with Parkinson's disease (PD) risk.Objectives: This study aimed to investigate in a large metaanalysis whether the LRRK2 Genome-Wide Association Study (GWAS) signal represented by rs76904798 is independently associated with PD risk from LRRK2 coding variation and whether complex linkage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Multiple independent risk variants were identified by GWASs in the LRRK2 region of European ancestry populations 8,28 , and this observation was confirmed in Chinese with LRRK2-A419V, LRRK2-G2385R, and LRRK2-R1628P showing associations independently. However, the risk variants of LRRK2 exhibited significantly different incidence across populations.…”
Section: Discussionmentioning
confidence: 79%
“…Multiple independent risk variants were identified by GWASs in the LRRK2 region of European ancestry populations 8,28 , and this observation was confirmed in Chinese with LRRK2-A419V, LRRK2-G2385R, and LRRK2-R1628P showing associations independently. However, the risk variants of LRRK2 exhibited significantly different incidence across populations.…”
Section: Discussionmentioning
confidence: 79%
“…Apart from that, the possibility that it is not necessarily the diagnosis of IBD but rather an associated inflammatory mediator that is associated with the risk of PD could not be ruled out with our MR study. A prior study showed that both rare and common variations at the leucine-rich repeat kinase 2 ( LRRK2 ) gene can influence PD susceptibility 18 , 19 . However, rare coding variants are not captured by GWAS studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the pathogenic (ie, Mendelian) LRRK2 variants, G2019S reigns king in Western PD populations with respect to combined effect size in disease risk and higher frequency as affirmed by whole‐genome sequencing efforts globally 22 . In the United States alone, more than 5000 people with PD are estimated to be G2019S carriers 22,23 . This sizable population suggests a sufficient global population to support concurrent therapeutic candidate efficacy studies, though their efficiency will benefit greatly from mounting efforts to introduce routine CLIA‐certified (Clinical Laboratory Improvement Amendments) PD gene testing into the clinic.…”
Section: Figurementioning
confidence: 99%
“…22 In the United States alone, more than 5000 people with PD are estimated to be G2019S carriers. 22,23 This sizable population suggests a sufficient global population to support concurrent therapeutic candidate efficacy studies, though their efficiency will benefit greatly from mounting efforts to introduce routine CLIA-certified (Clinical Laboratory Improvement Amendments) PD gene testing into the clinic. Moreover, there are other opportunities besides Mendelian LRRK2 variant carriers (eg, G2019S-LRRK2 carriers) to garner the apparent benefits genetic targets provide for drug approval likelihood.…”
mentioning
confidence: 99%